PRINCIPLES OF USING COMPUTER MODELS IN EDUCATIONAL PROCESSES (Scientific journal of the Fergana State University, 2024)
The content of this article is an analysis of educational methods aimed at organizing lesson processes based on innovative approaches in the field of education today. In particular, we consider the financial aspects of the important advantages of applying computer models to educational processes. In doing so, we will try to scientifically justify the positive and negative effects of computer models on educational processes. One of the main tasks is to improve the quality of lessons by promoting new approaches to learning processes and to ensure that learning processes are more effective for students.